IMPLEMENTATION OF THE USE OF FLASHCARD MEDIA IN IMPROVING ENGLISH VOCABULARY SKILLS OF ELEMENTARY SCHOOL STUDENTS - Zahra Mutiara; Afni Ajum Pulungan; Winda Khairiah; Nur Habibah; Bani Amirul (Publikasi Inspirasi Indonesia, 2024)
English at the elementary school level aims to enable students to develop communication competencies and have awareness of the essence and importance of English to increase the nation's competitiveness in a global society. To achieve this goal, basic skills are needed that students must master, namely in the form of English vocabulary skills, the more vocabulary a person has, the higher their language skills. Given the importance of the role of vocabulary in language, vocabulary learning is an important concern in learning English. Learning English vocabulary is not an easy thing because often students have difficulty in acquiring new vocabulary. The research method used is a qualitative research method with data collection techniques in the form of observation and documentation. The purpose of carrying out this study is to find out the implementation of the use of flashcard media in improving the English vocabulary skills of elementary school students. The result of this study is that flashcard media is quite effective for beginners to increase vocabulary and get used to English.